Effects of the Dark Septate Endophyte (DSE) Exophiala pisciphila on the Growth of Root Cell Wall Polysaccharides and the Cadmium Content of Zea mays L. under Cadmium Stress - Yao Xiao; Meng-Xue Dai; Guang-Qun Zhang; Zhi-Xin Yang; Yong-Mei He; Fang-Dong Zhan (Journal of Fungi, 2021)
This paper aims to investigate the mechanism by which dark septate endophytes (DSEs) enhance cadmium (Cd) tolerance in there host plants. Maize (Zea mays L.) was inoculated with a DSE, Exophiala pisciphila, under Cd stress at different concentrations (0, 5, 10, and 20 mg·kg−1). The results show that, under 20 mg/kg Cd stress, DSE significantly increased maize biomass and plant height, indicating that DSE colonization can be utilized to increase the Cd tolerance of host plants. More Cd was retained in DSE-inoculated roots, especially that fixed in the root cell wall (RCW). The capability of DSE to induce a higher Cd holding capacity in the RCW is caused by modulation of the total sugar and uronic acid of DSE-colonized RCW, mainly the pectin and hemicellulose fractions. The fourier-transform spectroscopy analysis results show that carboxyl, hydroxyl, and acidic groups are involved in Cd retention in the DSE-inoculated RCW. The promotion of the growth of maize and improvement in its tolerance to Cd due to DSEs are related to restriction of the translocation of Cd from roots to shoots; resistance of Cd uptake Cd inside cells; and the increase in RCW-integrated Cd through modulating RCW polysaccharide components.